Social Networking Sites Addiction and Psychological Well-Being - Bareera Nadeem Husain; Dr. Anamika Rai; Dr. Suruchi Bhatia (International Journal of Indian Psychȯlogy, 2025)
The virtual context in which young people are enmeshed must be considered in research on their well-being. The present study is designed and conducted keeping in mind that young people’s cyber dialogue is increasing year after year, in which social networking sites play a significant role. The aim of the study is to understand social networking sites (SNS) addiction and its relationship with psychological well-being. The study is conducted on a sample of 84 undergraduate students (18-30 years, N= 42 SNS addicted, and N=42 non-addicted) drawn through convenience sampling. Social Networking Addiction Scale by Ghazi Shahnawaz and Usama Rehman (2020) and Ryff’s Psychological Well-Being Scale (2007) are used to gather the data. Descriptive and inferential statistics are used to analyze the data. The Independent sample t-test also shows a significant difference between the psychological well-being of addicted and non-addicted undergraduates (p<0.05). Correlation analysis reveals a significant and negative correlation between social networking sites addiction and psychological well-being (p<0.01) for the overall sample. These findings highlighted a high usage of social networking sites during the pandemic. Besides, it is comprehended that there are negative consequences of the addiction to social networking sites on the well-being of young adults. These findings can be helpful in raising awareness among university students to manage their engagement with social networks.